2022
DOI: 10.1186/s12931-022-01990-2
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry parameters used to define small airways obstruction in population-based studies: systematic review

Abstract: Background The assessment of small airways obstruction (SAO) using spirometry is practiced in population-based studies. However, it is not clear what are the most used parameters and cut-offs to define abnormal results. Methods We searched three databases (Medline, Web of Science, Google Scholar) for population-based studies, published by 1 May 2021, that used spirometry parameters to identify SAO and/or provided criteria for defining SAO. We syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…8 In a review published in 2022, we found little consensus on the best spirometry parameter to use when measuring small airways obstruction. 9 Although FEF 25-75 is the most popular parameter, it is limited by high between-person variability, 10 whereas the FEV 3 /FVC ratio is a more suitable alternative, but it is scarcely used. 11 The rationale behind identifying small airways obstruction is its potential to act as a modifiable precursor to future obstructive lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…8 In a review published in 2022, we found little consensus on the best spirometry parameter to use when measuring small airways obstruction. 9 Although FEF 25-75 is the most popular parameter, it is limited by high between-person variability, 10 whereas the FEV 3 /FVC ratio is a more suitable alternative, but it is scarcely used. 11 The rationale behind identifying small airways obstruction is its potential to act as a modifiable precursor to future obstructive lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Spirometry parameters re ecting small airway function include FEV1, FEV 3 /FVC, MMEF, MEF50%, MEF25% [22,23]. Based on the Guideline for pulmonary function testing in primary care (2018) published by the Chinese Medical Association (CMA) and previous studies, SAD was diagnosed when at least two of these three indicators (MMEF, MEF50%, MEF25%) were less than 65% of predicted values in this study [23][24][25][26][27][28]. By spirometry, we identi ed that about 40% of IPF patients presented SAD signi cantly more frequently than the control group (21.0%).…”
Section: Discussionmentioning
confidence: 95%
“…As a measure of airflow limitation, FEF 25–75 is highly correlated with FEV 1 /FVC ratio, but non-linearly, so that FEF 25–75 decreases more steeply than FEV 1 /FVC at mild obstruction levels. We considered a FEV 1 /FVC ratio <70% as a marker of obstruction, 11 a FEF 25–75 <60% of predicted value as an expression of small airway dysfunction, 12 and an increase in RV/TLC ratio >20% as an indicator of lung hyperinflation. All subjects who exhibited a FEF 25–75 reduction, a normal FEV 1 /FVC ratio, and an increased RV/TLC ratio with symptoms of dyspnea upon exertion, were treated with a bronchodilator therapy consisting of GB at the dosage of 50 μg once a day for 4 months.…”
Section: Methodsmentioning
confidence: 99%